An integrated methodology to assess the operational and environmental performance of a conceptual regenerative helicopter - Ali, Fakhre; Goulos, Ioannis; Pachidis, Vassilios (Cambridge University Press, 2015)
This paper aims to present an integrated multidisciplinary simulation framework, deployed for the comprehensive assessment of combined helicopter powerplant systems at mission level. Analytical evaluations of existing and conceptual regenerative engine designs are carried out in terms of operational performance and environmental impact. The proposed methodology comprises a wide-range of individual modeling theories applicable to helicopter flight dynamics, gas turbine engine performance as well as a novel, physics-based, stirred reactor model for the rapid estimation of various helicopter emissions species. The overall methodology has been deployed to conduct a preliminary trade-off study for a reference simple cycle and conceptual regenerative twin-engine light helicopter, modeled after the Airbus Helicopters Bo105 configuration, simulated under the representative mission scenarios. Extensive comparisons are carried out and presented for the aforementioned helicopters at both engine and mission level, along with general flight performance charts including the payload-range diagram. The acquired results from the design trade-off study suggest that the conceptual regenerative helicopter can offer significant improvement in the payload-range capability, while simultaneously maintaining the required airworthiness requirements. Furthermore, it has been quantified through the implementation of a representative case study that, while the regenerative configuration can enhance the mission range and payload capabilities of the helicopter, it may have a detrimental effect on the mission emissions inventory, specifically for NOx (Nitrogen Oxides). This may impose a trade-off between the fuel economy and environmental performance of the helicopter. The proposed methodology can effectively be regarded as an enabling technology for the comprehensive assessment of conventional and conceptual helicopter powerplant systems, in terms of operational performance and environmental impact as well as towards the quantification of their associated trade-offs at mission level. Ali Fakhre, Ioannis Goulos, Vassilios Pachidis School of Engineering, Energy, Power and Propulsion Division, Cranfield University, Cranfield, Bedford, MK43 0AL, UK f.ali@cranfield.ac.uk The Aeronautical Journal, 2015, Vol 119, Issue 1211, pp1-24 Published by Cambridge University Press. This is the Author Accepted Manuscript. This article may be used for personal use only. The final published version (version of record) is available online at 10.1017/S0001924000010253. Please refer to any applicable publisher terms of use.